Pengaruh Olahraga Teratur Terhadap Kesehatan Jantung Dan Kebugaran Fisik - Nimrot Manalu; Miftahul Ihsan; Andes Martua; Nia Daniati; Berliana, Berliana; Bintang Panjaitan; Ezra Persada (CV. ITTC INDONESIA, 2025)
Exercise is one of the important factors in maintaining body health, especially in improving physical fitness and heart health. This study aims to analyze the effect of regular exercise on heart health and physical fitness. The research method used was an experiment involving 50 participants who were divided into two groups: an experimental group that did regular exercise for 12 weeks and a control group that did not do regular exercise. The results showed that participants who exercised regularly experienced a significant increase in aerobic capacity, more stable blood pressure, and decreased cholesterol levels. Thus, regular exercise can provide significant benefits for heart health and physical fitness.